Rekonstruksi Tujuan Pendidikan Islam Berbasis Taksonomi Transenden - Ah. Zakki Fuad (Islamica: Jurnal Studi Keislaman, 2015)
This article focuses on the reconstruction of the objective of Islamic education based on transcendent taxonomy. This study is based on the idea that ?the objective of Islamic education is to make students good?. The word ?good? becomes the key as well as the entrance to formulate the objective of Islamic education by examining the concept of ?good? in the Qur??n. The concept is studied using a model of thematic tafsir (mawd???) approach. Using this approach, the word ?good? is sought through three stems, i.e., the words ahsan-yuhsin, saluh-yasluh, and khayr with their various forms and changes in the Qur??n. The classification of verses uses the theory of taxonomy. This article reveals that the objectives of Islamic education taxonomy can be called the ?transcendent taxonomy.? The objectives of Islamic education based on the Qur?an can be classified into three dimensions: il?h?yah (theocentrism; divinity), ins?n?yah (anthro-pocentrism; humanity), and kawn?yah (cosmocentrism; naturality).